Management of Post-Disaster Medicine Logistics at the Pharmacy Installation of Regional Public Hospital Undata of Central Sulawesi Province - Bertin Ayu Wandira; Ketut Suarayasa; Kadek Viyan Kristiawan (Journal La Medihealtico, 2020)
The purpose of this research is to fine out how the management of post-disaster medicine logistics at the Pharmacy Installation of Regional Public Hospital Undata the research. Method used was qualitative with in-depth interview data cullcolection techniques. Research informants were 6 informants who were determined by purposive sampling technique. The results show that the planning of pharmaceutical supplies at Regional Public Hospital Undata used consumtion methods epidemiology. The obstacles to logistical planning for type medicine, a disease tread is changing. Medicine logistics budget in pharmaceutical installations comes from the state budget and BLUD. Procurement of pharmaceutical supplies using the method of direct purchases and E-purchasing, obstacles in the procurement of medicine logistic are still arrears of payment of medicine to distributors. Slow distribution of medicine from distributors and the emtiness of medicine stocks acceptance of pharmaceutical supplies is carried out by the pharmaceutical installation warehouse staff and reception team, there are still obstacles in receiving the time for quality inspection and quantity of logistical goods wich quite long. Medicine logistics storage is carried out with the FIFO and FEFO systems with alphabetical storage arrangements, constraints in logistics storage, narrow IFRS repositories. Medicine logistics control was done by taking inventory to find out the quality and quantity of medicine as well as the medicine expired date, the obstacles in controlling medicine logistics time to take stock of hospitalization takes a long time.